Linkage of a Population-Based Cohort With Primary Data Collection to Medicare Claims: The Reasons for Geographic and Racial Differences in Stroke Study - Xie, Fenglong (Am J Epidemiol, 2016)
We described the linkage of primary data with administrative claims using the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study and Medicare. REGARDS study data were linked with Medicare claims by use of Social Security numbers. We compared REGARDS participants by Medicare linkage status, having fee-for-service (FFS) coverage or not, and with a 5% sample of Medicare beneficiaries who had FFS coverage in 2005, overall, by age (45–64 and ≥65 years), and by race. Among REGARDS participants who were ≥65 years of age, 80% had data linked to Medicare on their study-visit date (64% with FFS coverage). No differences except race and sex were present between REGARDS participants without Medicare linkage and those with data linked to Medicare with and without FFS coverage. After the age-sex-race adjustment, comorbid conditions and health-care utilization were similar for those with FFS coverage in the REGARDS study and the 5% sample of Medicare beneficiaries. Among REGARDS participants aged 45–64 years, 11% had FFS coverage on their study-visit date. In this age group, differences were present between participants with and without FFS coverage and the Medicare 5% sample with FFS coverage. In conclusion, REGARDS participants aged ≥65 years with FFS coverage are representative of the study cohort and the US population aged ≥65 years with FFS coverage.